Learning, neurosis and stuttering - NS, Vishwanath (Journal of All India Institute of Speech and Hearing, 1970)
The field of learning has attracted considerable professional attention in the recent past. This is due to the fact that ’laws of learning’ have found wide application in the field of education and in the explanation and successful treatment of neurosis as learned behavior. The article intends to set forth the basic processes of Pavlovian and Skinnerian learning and to point out why and how neurotic behavior can be considered a learned behavior. The concluding part of the article relates to a brief consideration of stuttering as a maladaptive learned response